Synthesis, characterization, and swelling behavior of new pH-sensitive hydrogels derived from copolymers of 2-hydroxyethyl methacrylate and 2-(diisopropylamino)ethylmethacrylate - Faccia, Paula Andrea (2012)
The aim of this work was to synthesize and to characterize new pH-sensitive hydrogels that can be used in the controlled release of drugs, useful for dermal treatments or ophthalmology's therapies. Copolymers containing 2-hydroxyethyl methacrylate (HEMA) with different amounts of 2-(diisopropylamino)ethyl methacrylate (DPA) (10 and 30 wt %) and different amounts of crosslinker agent, ethylene glycol dimethacrylate (EGDMA) (1 and 3 wt %) were prepared by bulk photo-polymerization. The copolymers were fully characterized by using Fourier-transform infrared (FTIR) spectra, differential scanning calorimetry, thermogravimetric analysis, UV–visible spectroscopy, and measuring water content and dynamic swelling degree. The results show that modifications in the amount of DPA and/or crosslinker in the hydrogel produce variations in the thermal properties. When adding of DPA, we observed an increase in the thermal stability and decomposition temperature, as well as a change in the mechanism of decomposition. Also a decrease in the glass transition temperature was observed with regard to the value for pure pHEMA, by the addition of DPA. The water content of the hydrogels depends on the DPA content and it is inversely proportional to both the pH value and the crosslinking degree. Pure poly-HEMA films did not show important changes over the pH range studied in this work. The dynamic swelling curves show the overshooting effect associated with the incorporation of DPA, the pH of the solution, and the crosslinking density. On the other hand, no important variations in the optical properties were observed. The synthesized hydrogels are useful as a drug delivery pH-sensitive matrix.